Improvements in the prediction of the characteristic wave pattern of blunt ships with potential codes - Will, Johannes; Christiansen, Jakob (Volume 5: Ocean Engineering, 2013)
Potential flow solvers have been and still are the work horses of computational wave resistance determination. Having matured over more then two decades they seem to have reached their limit of improvement. While the main focus of today's software development lies on viscous flow solvers, the development of potential codes must not be disregarded, but they should instead be keep up to date with respect to the requirements of today's and future ship building markets as well as hardware and software capabilities.